HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANGAN TERHADAP KINERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH KOTA BEKASI - Kiki Deniati; Putri Yanti (Malahayati Nursing Journal, 2019)
ABSTRACT: STYLE OF LEADERSHIP TO THE PERFORMANCE OF NURSES IN THE INPATIEN WARD OF THE GENERAL HOSPITAL IN THE CITY OF BEKASI Backround: Leadership is the ability to influence people by setting goals for direction/command and motivation to work. The activities of leaders will show the pattern of leadership style applied in an organization can create a positive work effectiveness for members. Various kinds of leadership style of the head of the room is devided into 3 the leadership, authoritarian, democracy and laisez  faire, the style of leadership applied will affect the performance of nurses.Methods: This research uses analytic survey research design using cressectional approach. Population of 67 repondents with a sample of 60 respondents. Sampling technique using simple random sampling. Univariate and bivariate data analysis. Result: Univariate based research result, showed that leadership style of the majority of the head of democratic leadership style as much as 47 (78,3%) respondents. The performance of nurse implementers of the majority performs as much as 43 (71.7%). Bivariate analysis using chi square.The result showed (p value =0.000  α=0.05).Conclusion: significant relationship between leadership style and nurse performance. Keywords: Style of leadership, performance, nurse